1988
DOI: 10.1002/cm.970090304
|View full text |Cite
|
Sign up to set email alerts
|

Microtubules in ascidian eggs during meiosis, fertilization, and mitosis

Abstract: The sequential changes in the distribution of microtubules during germinal vesicle breakdown (GVBD), fertilization, and mitosis were investigated with antitubulin indirect immunofluorescence microscopy in several species of ascidian eggs (Molgula occidentalis, Ciona savignyi, and Halocynthia roretzi). These alterations in microtubule patterns were also correlated with observed cytoplasmic movements. A cytoplasmic latticework of microtubules was observed throughout meiosis. The unfertilized egg of M. occidental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 11 publications
3
32
0
Order By: Relevance
“…Reliable segregation of meiotic chromosomes depends on the correct assembly of microtubules (MTs) into a bipolar spindle. In most animal systems, female meiotic spindles lack centrosomes and their MT nucleating activity (Sawada and Schatten, 1988;Gard, 1992;Theurkauf and Hawley, 1992;Albertson and Thomson, 1993). Interestingly, vertebrate cultured cells in which centrosomes have been destroyed can use a centrosome-independent pathway to build a functional bipolar spindle (Khodjakov et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Reliable segregation of meiotic chromosomes depends on the correct assembly of microtubules (MTs) into a bipolar spindle. In most animal systems, female meiotic spindles lack centrosomes and their MT nucleating activity (Sawada and Schatten, 1988;Gard, 1992;Theurkauf and Hawley, 1992;Albertson and Thomson, 1993). Interestingly, vertebrate cultured cells in which centrosomes have been destroyed can use a centrosome-independent pathway to build a functional bipolar spindle (Khodjakov et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively few studies have examined the detergent-resistant cytoskeleton during early development. Those that have report the presence of an extensive detergent-resistant cytoskeletal network in eggs of a variety of species ranging from fresh water and marine organisms (24,35,37) to mammals (8). Much less, however, is known about the metabolic and structural role of the cytoskeleton during early development.…”
Section: Introductionmentioning
confidence: 99%
“…This is commensurat with the idea that segregation of myoplasm-specific molecules is brought about by cytoskeletal movement (24,11). Jeffery (10) reported that some maternal macromolecules, such as mRNAs and polypeptides, bound to the cytoskeletal lattice (12) and segregated to the yellow crescent.…”
Section: Discussionmentioning
confidence: 81%